Game Edukasi Pengenalan Bahasa Inggris Untuk Anak Usia Dini - Nining Ariati (UNIVERSITAS INDO GLOBAL MANDIRI)
Early childhood is a child who is at the age of 0-6 years, which is a very important age for child development or what is commonly called the golden period. Early childhood are in the most rapid stages of growth and development, both physically and mentally and they are learning in their own way. Currently, early childhood children are more interested in games that are on Android phones than other traditional games. They will also find it easier to remember something they like, and there are forms or writing that have interesting features and colors and are communicative and fun. Educational games are very interesting applications to be developed to overcome this problem. The advantages of educational games compared to conventional educational methods are to increase logic and understanding of a problem visually, and improve memory so that children can store subject matter for a longer time. The author makes an educational game on the introduction of English based on the Android operating system, with the hope that children can immediately use the game application and gain more knowledge and change learning patterns so that they are not bored and bored. This educational game for introducing English for early childhood consists of a menu for letter recognition, number recognition, animal recognition, counting and assessment. The benefit to be achieved from this research is to change conventional learning methods to simulated learning methods with mobile-based educational game media and to help students develop creativity because educational games have elements of challenge, accuracy, reasoning and ethics. If the child only knows English from where he is studying, it will take a long time for the child to memorize numbers, letters, and words in English. The existence of this educational game can be a fun and portable media to introduce English. So that children do not feel that they are learning but are playing words in English which can be done by themselves anytime at home. Children can learn on their own while playing at home so that children will memorize faster and get to know English well. Keywords : educational game, childhood, english, android